Incentives and Careers in Academia: Theory and Empirical Analysis - Checchi, Daniele; De Fraja, Gianni; Verzillo, Stefano (The Review of Economics and Statistics, 2021)
Abstract We study career concerns in italian academia. We mold our empirical analysis on the standard model of contests, formalized in the multiunit all-pay auction. The number of posts, the number of applicants, and the relative importance of the criteria for promotion determine academics' effort and output. In Italian universities, incentives operate only through promotion, and all appointment panels are drawn from strictly separated and relatively narrow scientific sectors. Thus, the parameters affecting payoffs can be measured quite precisely, and we take the model to a newly constructed data set that collects the journal publications of all Italian university professors. Our identification strategy is based on a reform introduced in 1999, parts of which affected different academics differently. We find that individual researchers respond to incentives in the manner described by the theoretical model: roughly, more capable researchers respond to increases in the importance of the publications for promotion and in the competitiveness of the scientific sector by exerting more effort; less able researchers are discouraged by competition and do the opposite.